Has the establishment of national parks improved nature-based tourism experiences? Evidence from social media data - Yi Li; Yitong Yang (PLoS ONE, 2026)
National parks are vital institutions for conserving biodiversity and preserving biocultural heritage that safeguard exceptional natural resources and sustain key cultural ecosystem services (CESs), such as aesthetic appreciation, nature-based recreation, and environmental education. However, the essentially subjective and intangible characteristics of CESs are obstacles to effectively collecting data and measuring their diverse values. This study developed a supply–support–demand framework for analyzing nature-based tourism in national parks, using Giant Panda National Park, one of China’s earliest national parks, as the case study site for the years 2009–2023. To investigate the impact of national park establishment, we employed a difference-in-differences (DID) approach to assess its effects on counties within national parks. We found that tactile and visual impressions play a key role in shaping visitors’ experiences, whereas olfactory, gustatory, and auditory perceptions exhibit cooccurring, supportive influences on visual and tactile impressions, as revealed through the rich expressions captured in social interactions. The establishment of national parks has the potential to enhance nature-based tourism experiences by increasing local fiscal expenditure and expanding the tourism industry. The effects exhibit clear regional heterogeneity and differences in policy intensity. At the regional level, Sichuan and Shaanxi, regions with relatively stronger infrastructure and resource endowments, show better improvement in nature-based tourism experiences, whereas Gansu shows an insignificant effect. In terms of policy intensity, stronger interventions are accompanied by stricter ecological protection constraints. As a result, the improvement in nature-based tourism experiences is significantly greater in the low-intensity policy group than in the high-intensity policy group.